Penerapan Model Snowball Throwing Dalam Meningkatkan Hasil Belajar IPS Siswa Kelas V SD Inpres Kampung Mejang Di Kecamatan Bontonompo Kabupaten Gowa - Sri Rahayu Agustina; Syarifah Aeni Rahman; Rubianto Rubianto (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The problem in this study is the low social studies learning outcomes for fifth grade students at SD Inpres Kampung Mejang in Bontonompo District, Gowa Regency. This study aims to determine the increase in social studies learning outcomes through the application of the snowball throwing model to fifth grade students at SD Inpres Kampung Mejang in Bontonompo District, Gowa Regency. This type of research is Classroom Action Research (PTK) which is carried out in two cycles and each cycle is held in three meetings. Each cycle in this study went through 4 stages, namely, the planning stage, the implementation stage, the observation stage, and the reflection stage. The subjects in this study were 28 grade V students of SD Inpres Kampung Mejang. Data collection techniques used are observation, tests and documentation. The data analysis technique used is descriptive statistical analysis. Based on the analysis of learning achievement test data in cycle I, out of 28 students, only 7 students passed with a learning completeness percentage of 25% and those who did not meet the minimum completeness criteria (KKM = 70) were 21 students with a learning completeness percentage of 75% with an average score overall students in cycle I is 58.85. In cycle II the number of students who passed increased to 24 students with a complete learning percentage of 85.71% and the number of students who did not meet the KKM was 4 students with a percentage of 14.28% with an average overall student score in cycle II of 80.78. The conclusion in this study is that through the application of the snowball throwing model it can improve social studies learning outcomes in fifth grade students at SD Inpres Kampung Mejang in Bontonompo District, Gowa Regency.